In-situ investigation of multiple endothermic peaks in isomorphous poly(3-hydroxybutyrate-co-3-hydroxyvalerate) with low HV content by synchrotron radiation. (15th April 2019) - Zhu, Hao; Lv, You; Duan, Tianchen; Zhu, Mengjie; Li, Yiguo; Miao, Weijun; Wang, Zongbao
Abstract: Multiple endothermic peaks of isomorphous P(HB-co-HV) with low HV content were investigated by DSC, in-situ WAXD and SAXS measurements. The multiple endothermic peaks are confirmed to be caused by two different kinds of crystal structures of P(HB-co-HV), namely uniform lamellae with HV units complete exclusion and sandwich lamellae with HV units partial inclusion. With the increase of the temperature, the thinner uniform lamellae melt at the lower melting peak and the thicker sandwich lamellae melt at the higher melting peak. Comparing with P(HB-co-4.9%HV), P(HB-co-9.4%HV) has the larger value of unit cell parameters and the higher distribution and fusion enthalpy of higher melting peak, which confirm that P(HB-co-HV) with higher HV content contains more sandwich lamellae and more HV units included in crystals for P(HB-co-HV) with HV content lower than 10 mol%. Graphical abstract: Image 1 Highlights: Multiple endothermal peaks of isomorphous P(HB-co-HV) caused by two crystal structures. The thinner uniform lamellae with HV units exclusion melt at lower temperature. The thicker sandwich lamellae with HV partial inclusion melt at higher temperature. P(HB-co-HV) contains more sandwich lamellae with HV content increasing.